Effect of white and monochromatic lights on cyanobacteria and biofilms from Roman Catacombs. (September 2017) - Bruno, Laura; Valle, Veronica
Abstract: Phototrophic biofilms are widespread in Roman Catacombs due to the favourable microclimatic conditions present in these hypogea. They consist of complex communities formed by cyanobacteria and microalgae along with some heterotrophs embedded in a common mucilaginous matrix and are responsible for the aesthetic and structural deterioration of these important sites. It is a common practice to treat these surfaces with mechanical brushes and/or biocides in order to eradicate the presence of microorganisms. However, these treatments are not very efficient in the long term. In this study, research was carried out in order to understand which wavelengths of light inhibit the growth of phototropic biofilms and cyanobacterial strains isolated from Roman Catacombs and to develop a new illumination system. LEDs with various ranges of emission were employed along with a LED -'testing light', that appeared white to the human eye, obtained from a combination of wavelengths. The 'testing light' inhibited microbial growth and thus appeared a good candidate for the development of new illumination systems in confined environments to prevent biodeterioration. Highlights: Phototrophic biofilms caused deterioration problems in Roman Catacombs. Research was carried out to investigate which wavelengths inhibit their growth. To develop and employ new LED illumination system with various emissions. A 'testing light', that appeared white to the human eye, was obtained and tested. The 'testing light' showed good results in the inhibition of the microbial growth.